Re-shaping the political space: continuity and alignment of parties in the Italian parliament. Issue 2 (3rd April 2019) - Ieraci, Giuseppe
ABSTRACT: This article adopts an inductive approach to the study of party positions in the Italian Parliament during the centre-left governments of Enrico Letta (2013–2014) and Matteo Renzi (2014–2016), as they emerge from the investiture vote. This is a unique moment in the relationship between Parliament and Government because the parliamentary groups debate the Government's programme before delivering their first confidence vote. The research aim is to assess the alignment of the Italian parties in Parliament following the decline of the traditional left-right cleavage and the rise of populism. A content analysis of the texts of the speeches delivered during the parliamentary debate before the confidence votes confirming the investiture of the Letta and Renzi governments provides a survey of the political themes addressed by the latter and by the main Italian parliamentary groups. The findings highlight the multidimensional character of the competition space and show how party alignment is affected by the interplay between the supranational dimension (European integration) and the state's capacity to provide services and guarantee citizens' rights. It is argued that the emergence of new parties has favoured the re-establishment of a multi-polar pattern of competition, but without clear ideological connotations, in contrast with the situation of the earlier post-war period.